Endocrine treatment in breast cancer: Cure, resistance and beyond. (November 2016) - Tryfonidis, Konstantinos; Zardavas, Dimitrios; Katzenellenbogen, Benita S.; Piccart, Martine
Highlights: Hormone-receptor positive breast cancer constitutes the most frequent subtype. Clinical and molecular research is intense in this subtype. Resistance can eventually develop despite effective therapy. New drugs have entered in our therapy armamentarium. Future holds better tailoring of endocrine treatment. Abstract: Hormone receptor positive breast cancer (HR-positive BC) is the most frequent BC subtype (∼70%), with endocrine treatment constituting its therapeutic cornerstone; despite its efficacy, endocrine resistance can develop, clinically as a relapse or a progression of the early or advanced disease respectively, hence necessitating alternative treatments. Over the last two decades, improved understanding of the molecular mechanisms of endocrine resistance has been achieved, with numerous targeted agents undergoing clinical development. Despite the multifactorial genesis of endocrine resistance, fuelled not only by alternative oncogenic signaling pathways of tumor cells, but also by tumor microenvironment-mediated mechanisms, successful clinical development of new agents has been recently noted. However, predictive biomarkers for accurate 'navigation' across the different treatment options are urgently needed. In this article, we present a thorough overview of the different clinical scenarios of BC endocrine resistance, and the recent advances in endocrine treatment, we describe the basic molecular mediators of endocrine resistance and the respective targeted agents undergoing clinical development; finally, we provide our perspective on the future of BC endocrine treatment.